Population policy for India perspectives, issues and challenges - Chaubey, P K (New Delhi Kanishka Publishers Distributors, 2001)
Population policy for India is divided in five parts. Pt.-1 provides besides an essential of population policy.Part-2 deals with history. Part-3 deals with pre-independence efforts part-4 is on perpectives and part-5 appends documents on population policy
Keywords: India-Population policy; Demogrpahy